INTERNALISASI IMAN DAN TAQWA DALAM MEWUJUDKAN KEHIDUPAN SOSIAL DI LINGKUNGAN MASYARAKAT - Purmansyah Ariadi; Rulitawati Rulitawati; Yuniar Handayani; Rijalush Shalihin (Raudhah - Proud To Be Professional, 2024)
Abstract: Internalizing faith and Taqwa in everyday life is an important process in forming a personality with noble and responsible morals. Faith is belief in God Almighty, while Taqwa is the awareness to always carry out His Commands and avoid His prohibitions, these are the two main pillars for building a more meaningful and quality life. The internalization of religious values ​​is not only limited to the spiritual aspect, but also includes implementation in attitudes, behavior and social interactions. The aim of this research is to reveal how the internalization of faith and piety can form more meaningful human life values ​​in realizing the goal of human life to be happy in this world and the hereafter. Methods in field research (field research) with data analysis techniques using descriptive qualitative data collection through observation, interviews with the community and the study community in Payo Besar village and supported by documentation data. This research results, firstly with the existence of a routine study program in the Payoh Besar district that creates a harmonious life in the community. Second, make the Mosque a place of worship and more active religious activities so that the life of the community is always active in commemorating the great days of Islam as well as other activities. With the application of the values ​​of faith and piety, each individual is expected to be better, in Aqidah, Worship, patient, and oriented towards the common good. Therefore, the cultivation of the internalization of faith and piety is very important in religious education in social life which can be implemented through family education, formal education and the community environment. Keywords: : Internalization, Faith and Taqwa, Society